2016
DOI: 10.1007/s11356-016-7019-0
|View full text |Cite
|
Sign up to set email alerts
|

BTX in urban areas of eastern Spain: a focus on time variations and sources

Abstract: Seasonal and daily cycles of BTX were studied in a non-industrialized city (Alicante) and an urban area near an oil refinery plant (Castellón) in order to evaluate the influence of different sources on time variations. Lower levels were observed in summer than in winter at both locations due to higher dispersion conditions and photochemical removal of BTX during the summer season. Daily patterns showed seasonal differences and were controlled by traffic emissions and the evolution of the mixing layer height, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
4
0
0
Order By: Relevance
“…Benzene concentrations for both sampling sites were similar to those found in Athens [40] and Hong Kong [40] but lower than those registered in Ankara [3]. Toluene levels in Cholul and SEDUMA (this study) were similar to those reported for Alicante and Castellon [41]. Ethylbenzene showed concentrations similar to those found in Athens [42] and higher than those reported for Hong Kong [40], Monterrey [43] and Ankara [3].…”
Section: Btex Correlations Ratios and Principal Component Analysis Rsupporting
confidence: 83%
See 1 more Smart Citation
“…Benzene concentrations for both sampling sites were similar to those found in Athens [40] and Hong Kong [40] but lower than those registered in Ankara [3]. Toluene levels in Cholul and SEDUMA (this study) were similar to those reported for Alicante and Castellon [41]. Ethylbenzene showed concentrations similar to those found in Athens [42] and higher than those reported for Hong Kong [40], Monterrey [43] and Ankara [3].…”
Section: Btex Correlations Ratios and Principal Component Analysis Rsupporting
confidence: 83%
“…Ethylbenzene showed concentrations similar to those found in Athens [42] and higher than those reported for Hong Kong [40], Monterrey [43] and Ankara [3]. This study showed p-xylene concentrations higher than those found in Alicante [41], Castellon [41], Algiers [44] and Ankara [3], but lower than those reported for Greater Cairo [36]. …”
Section: Btex Correlations Ratios and Principal Component Analysis Rsupporting
confidence: 63%
“…Similarly to NO x , the concentrations of traffic-related volatile organic compounds, such as benzene, toluene and xylenes ( Galindo et al, 2016 ; Lu et al, 2017 ) decreased during the lockdown in 2020 compared with the same span in 2019, as observed in other studies ( Jianxin et al, 2021 ). For example, the mean concentration of toluene (the most abundant of the measured hydrocarbons) during the quarantine in 2020 (0.9 ± 0.6 μg m −3 ) was half that measured during the same time period in 2019 (1.9 ± 0.9 μg m −3 ).…”
Section: Resultssupporting
confidence: 67%
“…Table 2 shows a comparison of the average concentrations reported in this study with similar analyses reported for other locations around the world. Benzene concentrations in the three monitoring campaigns were similar to those obtained in North Poland by Marć et al [46] and in Alicante, Spain by Galindo et al [47], but lower than those reported by Liu et al [48] in Jinan, China, and by Singh et al [29] in Delhi, India. Alicante, Spain has similar population, population density and sources as compared to our study site ( Table 2).…”
Section: Results For C 1 -C 2 Carbonylssupporting
confidence: 84%